The Development of Effective Clinical Teaching Model (ECTM) and The Effects to Self Efficacy of Nurse Clinical Instructors in Jakarta State Hospital - Kurniadi, Anwar; Sitorus, Ratna; Waluyo, Agung; Prasetyo, Sabarinah (Technium BioChemMed, 2021)
Self-efficacy of clinical nurse instructors (CNI’s) could improve the socialization of nursing professionals of nursing students, whereas, on the fact that their self-efficacy was still low. The purpose of this study was to know the effect of an effective clinical teaching model on knowledge, attitude, and self-efficacy of CNI’s. The second step used a pre-post test with control group design, to know the effects of an effective clinical teaching module (ECTM) by training toward knowledge, attitudes, and self-efficacy. The sampling method used consecutive sampling that included 74 CNI’s (37 intervention and 37 control). The research result showed that ECTM training: 1) could improve significantly (P-value 0,00), the variable knowledge, attitudes, and self-efficacy; 2) knowledge variable most affected (77%). The conclusion was the ECTM training significantly improved knowledge, attitudes, and self-efficacy of CNI’S, and knowledge was the most affected variable.